Humans’ Body Immunity and Natural Pigments - Indrawati, Renny; Limantara, Leenawaty; Brotosudarmo, Tatas H.P. (Ma Chung Research Center for Photosynthetic Pigments, 2020)
The emerging pandemic of Corona Virus Disease (COVID-19) has attracted special concerns regarding the case of very contagious viral infection. Besides the profound waiting toward vaccine development, public awareness was also addressed into the effort of increasing humans’ body immunity. Nowadays, the people are encouraged to consume adequate amount of vitamin C and increase the consumption of fruits and vegetables. In addition, various kinds of food supplements are offered and claimed to give us protection and prevention against viral infection by boosting our immune system. However, the communities are actually lack of proper information regarding the true mechanism of immune system. How is the infection developed in our body? How does the immune system work? Could it be modulated by consuming the bioactive compounds? Here, the stages of infection, the immune system, as well as the role of natural pigments to support the humans’ body immunity will be briefly discussed.